17 beta-estradiol modulates endothelin-1 expression and release in human endothelial cells - (:unkn) unknown (ELSEVIER SCIENCE BV, 2000)
Objective: In this study the role of 17 beta-estradiol (E2) in the regulation of endothelin-1 (ET-1) mRNA expression and secretion was investigated in cultured human umbilical vein endothelial cells (HUVECs). Methods: Endothelial cells were either deprived of or treated with 17 beta-estradiol (10(-9), 10(-7) M) for 48 h. After the incubation, the effect of E2 on ET-1 gene expression was evaluated by Northern blot analysis. ET-1 release into the media was measured by radioimmunoassay after 6 h of incubation under basal conditions and upon stimulation with thrombin (4 U/ml). In addition, the cyclic guanosine 5'-monophosphate (cGMP) content of cells was assayed by immunoassay. In order to exclude the role of nitric oxide (NO) in E2-induced effects on endothelin-1 gene expression and secretion, nitric oxide synthase (NOS) inhibitor, N-nitro L-arginine methyl ester (1 mM) (L-NAME) was added to the media of some cultures. Results: Incubation of HUVECs with 10(-9) and 10(-7) M E2 for 48 h resulted in a 30 and 47% inhibition of ET-1 mRNA expression, respectively. Incubation with E2 also decreased the basal and thrombin-stimulated ET-1 release while increasing the cGMP content of cells significantly. NOS inhibitor L-NAME increased the release of ET-1 from E2-incubated cells but did not alter the ET-1 release from hormone-deprived cells. However, ET-1 secretion of E2-treated cells were significantly less than the deprived ones. Northern blot analyses also demonstrated that inhibition of NOS only partly attenuated the effect of E2 on ET-1 gene expression. In the presence of L-NAME, treatment with 10(-7) M E2 caused a 12% decrease in ET-1 gene expression. Conclusion: The results demonstrate that E2 may play both direct and indirect role in regulation of ET-1 gene expression and production in human endothelial cells. E2-induced increase in NO but decrease in ET-1 production may partly explain the mechanism of the protective effects of the hormone on the cardiovascular system. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: endothelial function; endothelins; nitric oxide; hormones; gene expression; NITRIC-OXIDE; POSTMENOPAUSAL WOMEN; CORONARY-ARTERIES; ESTROGEN; RESPONSES; THROMBIN; PEPTIDE; AORTA; INHIBITION; MECHANISMS